KEHIDUPAN SOSIAL EKONOMI MASYARAKAT BUKIT RIMBO TAKURUANG KORONG KOLAM JANIAH NAGARI KUDU GANTIANG KECAMATAN V KOTO TIMUR KABUPATEN PADANG PARIAMAN PASCA BENCANA ALAM TANAH LONGSOR (2007-2012) - efriyani, Riska; Husnita, Liza; Nurhuda, Ahmad (Pendidikan Sejarah, 2013)
ABSTRACTNatural disasters such as landslides have left deep wounds and traumatic for the people living around the landslide-prone zones, as well as in Korong Kolam Janiah Nagari Kudu Gantiang V Koto Timur District, Padang Pariaman regency. Nature disasters landslides that occurred on 8 January 2007 that has killed 13 people, 4 houses and 1 mosque. This paper examines the nature landslide disaster in 2007. Historical research methods : ( 1 ) Heuristics ( 2 ) Source Criticism ( 3 ) Interpretation ( 4 ) Historiography . Based on the results of the research showed that citizens affected by natural disasters landslides change. Social capital in building a house is affected by the birth of a sense of community, kinship, but there is also in the form of exchange of the good or service. While the economic impact of a society that is seen as the majority of farmers are now no longer just rely on one principal livelihood, but also take advantage of other employment opportunities in order to increase revenue and income to meet their daily living needs. The conclusion of this study is that public life after landslide occurrences has improved and has returned to usual activities.Â Keyword : socioeconomic communities after nature disasters landslide